Gendering ‘Child’ Poverty: Cross-National Lessons for Canada in a Deepening Recession - Baker, Maureen (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
As the world slides deeper into recession, ‘child poverty’ rates will undoubtedly increase with rising unemployment, household debt and marriage breakdown. This comparative paper focuses on the gendered aspects of child poverty, showing that Canada has higher rates of maternal employment than some other liberal welfare states but also higher poverty rates for mother-led families, a larger gender gap in pay, and lower levels of social spending on families. The paper argues that the lack of gender analysis in political discourse tends to downplay the well-known association between poverty and female-led households, which requires greater acknowledgement as the recession worsens.